A systems approach for green public procurement implementation. Issue 3 (30th April 2020) - Wang, Conghu; Qiao, Yuhua; Li, Xiaoming
Abstract : Purpose: This paper aims to identify important factors in green public procurement (GPP) implementation and then to clarify how these factors affect GPP implementation. Design/methodology/approach: The authors applied the Delphi method first and then conducted a focused and constrained multiple case study at 18 government procurement centers across China. Findings: The authors identified four clusters of factors for successful GPP implementation: more clear, consistent and operational policy goals; a nation-wide green procurement campaign to enhance social capital and cultural resources; promoting staff's ethics, professionalism, capacity and knowledge; and establishing checks and balances among organizations involved in the whole purchasing process. Social implications: GPP can significantly improve environmental protection and sustainable development. Originality/value: Based on key insights from systems theory and agency theory, the authors emphasize that GPP implementation must take down its own functional silos and adopt a process approach across organizational tiers to synchronize human resource based and inter-organizational capabilities into a unified whole through information sharing, communications and collaboration.